THE SINGLE-STAGE AND DELAYED RECONSTRUCTIVE PLASTY IN BREAST CANCER PATIENTS - Ye. M. Bit-Sava; S. G. Balandov; R. M. Akhmedov; M. A. Monogarova (Вестник хирургии имени И.И. Грекова)
An absence of breast is the irreversible cosmetic and physical defect, which reduces the self-assessment and psyco-emotional status of women. Nowadays the necessity of reconstruction after mastectomy will gain more popularity and plays a fundamental role in psychological and social rehabilitation of breast cancer patients. The article analyzes the experience of reconstructive plasty of 26 patients with I–III stages of breast cancer.